Sustainable Local Livelihoods through Enhancing Agroforestry Systems in Nepal - Hari Pandit, Bishnu; Shrestha, Krishna Kumar; Bhattarai, Suman S. (Journal of Forest and Livelihood, 2024)
Agroforestry has been recognized as one of the important systems for supporting the livelihoods of a large number of rural farmers in the Nepalese hills. However, its conservation and socio-economic values have received little attention. There is no solid information that tells us precisely how the agroforestry system has changed over time and what its drivers are in terms of biodiversity conservation and livelihood improvement. This paper aims to investigate the changing impacts and drivers of the agroforestry system to improve people’s livelihoods and deliver the outcomes of biodiversity conservation. This research analyses a case study of two Village Development Committees, viz Mahadevsthan and Mithinkot, in Kavrepalanchok district in Nepal. The mixed method approach was employed to collect data. The results indicate that the agroforestry system has changed considerably over time. As a result, the number of agroforestry species has increased in private lands. A total of 145 different species were recorded, of which 56 species were medicinal plants, followed by fodder trees, grasses and fruit trees. The study further found that species richness has increased, mostly in upland terraces. This resulted in increased livelihood benefits to local people. Production of goat meat and buffalo milk has increased considerably. The high economic benefits are mainly associated with the introduction of various fodder trees and grasses in private farmlands. It is concluded that the various drivers of the agroforestry system need to be carefully attended so as to improve both positive conservation and livelihood outcomes. Enabling policy and practices are needed to initiate and support farming cooperatives in the commercialization of agroforestry products and market the conservation values in a changing climate.